How diverse are national banking systems? An analysis on banking business models, profitability, and riskiness. (5th November 2019) - Caterini, Giacomo; Gaffeo, Edoardo; Gobbi, Lucio
Abstract: In this paper, we apply an algorithm developed by Martin Weitzman to quantify the extent of diversity among the business models of financial intermediaries at an international level. In particular, we investigate the relationship between the diversity of the business models of EU national banking systems and their profitability and riskiness. We show how Weitzman's approach can be generally applied to the issue at hand; as a by‐product, the analysis allows us to assess whether the diversity among banking systems was affected by the imported systemic financial crises of 2007/8 as well as its domestic sequel centered on the sovereign debt crisis that occurred in 2010–12. The motivation for this paper is twofold. First, we provide an operational measure of the diversity of business models among banking sectors. Second, we enrich the economic literature relating to banking business models by providing a macro‐founded analysis. To this end, we highlight the range of diversity of national banking business models correlated with high performances in terms of profitability and riskiness.